Investor Overconfidence and Disposition Effect : An Evidence from India - Sushmita; Bhatia, Rishabh; Sharma, Sanchit (Indian Journal of Research in Capital Markets, 2018)
Behavioral finance, as a field of study, has emerged in order to explain the irrationality exhibited by investors in the financial markets to better understand the market and formulate trading and investing strategies. This study aimed to delve into the behavioral biases present in the Indian financial system and their impact on the same. The study focused on quantifying the influence of overconfidence and disposition effect on the Bombay Stock Exchange. These biases lead to outcomes that were inconsistent with the outcomes obtained by applying the traditional expected utility theory. Analysis was done by finding the relationships between the volume of stock traded, stock returns, and the market returns using basic OLS regression on lagged values of these variables. The analysis suggested that disposition effect and overconfidence were extant in the Indian stock market (BSE SENSEX, in particular) and had huge bearing on the investors’ decision making. Also, apart from the basic fundamental and technical analysis, an investor’s decision is driven by heuristics and mental biases, which shows that there is no particular mathematical formula to arrive at the investment decision taken by investors. It also suggested the need to formulate algorithms and trading strategies which take into account the impact of theseÂ biases and also to enhance accuracy. The results of this study were found to be in tandem with many other research studies and revealed that India is no exception when it comes to biases.